Seroprevalence Study of Pertussis in Adults at Childbearing Age and Young Infants Reveals the Necessity of Booster Immunizations in Adults in China - Chen Zhiyun; Pang Jie; Zhang Nan; Chen Ning; Ding Yiwei; He Qiushui (MDPI, 2022)
In China, the vaccination strategy against pertussis is started from 3 months of age, with no booster dose used after the booster given at two years. Despite a high vaccination coverage, pertussis has been increasingly reported since the last decade. This study evaluates the prevalence of serum anti-pertussis toxin (PT) IgG antibodies in adults at childbearing age and infants before the age of primary immunization in Beijing, China. A total of 1175 serum samples randomly selected from individuals who attended an annual health examination at the Sixth Medical Center of the PLA General Hospital, Beijing, in 2019, was included. The geometric mean concentration (GMC) and median concentration of anti-PT IgG antibodies among adults aged 20-39 years were 3.81 IU/mL and 3.24 IU/mL, and the corresponding concentrations were 1.72 IU/mL and 1.43 IU/mL among infants under 3 months of age. The seroprevalence of PT IgG antibodies >= 40 IU/mL in adults and infants was 2.0% (15/735) and 1.1% (5/440). In total, 65.99% (485/735) of adults and 83.41% (367/440) of infants had non-detectable pertussis-specific antibodies (<5 IU/mL). Our results showed that the majority of adults at a reproductive age and young infants are vulnerable to pertussis, suggesting that booster vaccinations in adults should be considered in this country.